QUS of phalanx, DXA, BMD, Osteoporosis - A Soltani; R Hafezi; A Keshtkar; Z Hamidi; *B Larijani (Tehran University of Medical Sciences, 2004)
DXL of calcaneus is a portable method for BMD. This study determined a cut off point for DXL in osteoporosis diagnosis. In 510 healthy postmenopausal women, BMD of axial regions with DXA (DPX-MD, GE,Lunar Corp, Madison, WI) and heel with DXL (Demeteck- Sweden), measured. The agreement of two methods and cut off point for DXL in defining osteoporosis, obtained. DXA found osteoporosis in 34.3% and in DXL in 26.1% of cases. Agreement (Kappa) was 0.407 for spine and 0.347 for femur. T-score = -1.8 for spine and T-score = -2.2 for femur were the cut off points of DXL in diagnosis of osteoporosis (sensitivity=84% specificity=60%) and (sensitivity=84% and specificity=70%), respectively. Area under curve for regions were 0.807 (P=0.000) and 0.859 (P=0.000), respectively. These results mean DXL can not be used as a replacement for DXA, but it may can be used as a screening method for osteoporosis.